In vitro spatially organizing the differentiation in individual multicellular stem cell aggregates. (2nd January 2016) - Qi, Hao; Huang, Guoyou; Han, Yu Long; Lin, Wang; Li, Xiujun; Wang, Shuqi; Lu, Tian Jian; Xu, Feng
Abstract: With significant potential as a robust source to produce specific somatic cells for regenerative medicine, stem cells have attracted increasing attention from both academia and government. In vivo, stem cell differentiation is a process under complicated regulations to precisely build tissue with unique spatial structures. Since multicellular spheroidal aggregates of stem cells, commonly called as embryoid bodies (EBs), are considered to be capable of recapitulating the events in early stage of embryonic development, a variety of methods have been developed to form EBs in vitro for studying differentiation of embryonic stem cells. The regulation of stem cell differentiation is crucial in directing stem cells to build tissue with the correct spatial architecture for specific functions. However, stem cells within the three-dimensional multicellular aggregates undergo differentiation in a less unpredictable and spatially controlled manner in vitro than in vivo . Recently, various microengineering technologies have been developed to manipulate stem cells in vitro in a spatially controlled manner. Herein, we take the spotlight on these technologies and researches that bring us the new potential for manipulation of stem cells for specific purposes.